2011
DOI: 10.4067/s0718-58392011000400003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Relative Cell Injury Percentage and Some Yield Contributing Traits in Wheat Under Nomral and Heat Stress Conditions

Abstract: Several wheat genotypes were screened against heat stress. Seven wheat (Triticum aestivum L.) cultivars obtained after screening against heat classified as tolerant, moderately tolerant, and susceptible to heat stress, were mated in a complete diallel mating system to study the inheritance pattern of relative cell injury percentage (cell injury %) and some yield contributing parameters under normal and heat stress conditions. Significant genotypic differences were found (P < 0.01) for all the studied traits un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 24 publications
6
9
0
Order By: Relevance
“…High heritability and genetic advance estimates show that this trait can be improved through sensible selection among these crosses. The results of the present research are in agreement with the findings of Chowdhry et al (1997), Khan et al (2003), Ahmed et al (2004) and Farooq et al (2011).…”
Section: Days To Headingsupporting
confidence: 93%
“…High heritability and genetic advance estimates show that this trait can be improved through sensible selection among these crosses. The results of the present research are in agreement with the findings of Chowdhry et al (1997), Khan et al (2003), Ahmed et al (2004) and Farooq et al (2011).…”
Section: Days To Headingsupporting
confidence: 93%
“…These findings correspond with the results published by other authors who also indicated over-dominance type of gene action in the inheritance of the trait grain weight per plant (Nazir et al, 2014;Yao et al, 2014;Shehzad et al, 2015). Contrary to these results, partial dominance in the inheritance of this trait was observed by Farooq et al (2011) and Rashid et al (2013).…”
Section: Graphical Representation For the Traitssupporting
confidence: 91%
“…Also, Asif et al (2000) and Pal and Kumar (2009) found that biological yield was managed by the overdominance type of genes in wheat and barley, respectively. A significantly higher value of additive than dominance genetic components indicated the additive type of gene action in controlling biological yield in wheat (Farooq et al 2011). A greater value of the average degree of dominance than unity was reported for biological yield in F 2 populations of wheat (Jadoon et al 2012).…”
Section: Discussionmentioning
confidence: 92%
“…Solomon and Abuschagne (2004) reported high heritability for days to heading, which might be due to the involvement of few major genes in durum wheat. High heritability was reported for days to heading in genetic analysis for earliness-and yield-associated traits in spring wheat under normal and stress environments (Farooq et al 2011).…”
Section: Discussionmentioning
confidence: 98%